2018
DOI: 10.4103/ccd.ccd_64_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pneumatized articular tubercle using panoramic radiography and cone beam-computed tomography: A retrospective study

Abstract: Context:In 1985, Tyndall and Matteson first described the air cells that occur in the root of zygomatic arch and in the articular eminence of the temporal bone but do not extend beyond the zygomaticotemporal suture.Aims:The aim is to study the prevalence and patterns of pneumatized articular tubercle (PAT) retrospectively using two different imaging modalities, i.e., digital panoramic radiography and cone-beam computed tomography (CBCT).Subjects and Methods:Total 3000 panoramic radiographs belonging to 1291 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Interestingly in the present study, both locularity types were observed in one patient. Bhalchim et al reported two patients who had unilocular on side and multilocular on the other side (11). The detailed results of previous studies are showed in Table 3.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly in the present study, both locularity types were observed in one patient. Bhalchim et al reported two patients who had unilocular on side and multilocular on the other side (11). The detailed results of previous studies are showed in Table 3.…”
Section: Discussionmentioning
confidence: 95%
“…Bhalchim et al [21] found unilocular PAT to be more prevalent on panoramic radiographs and multilocular PAT to be more prevalent on CBCT scans. is difference may be attributed to the fact that CBCT provides more detailed images of the temporal bone and panoramic radiographs are negatively affected from superimpositions and distortion of the evaluated area.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Pneumatization is a normal physiological process. [21] In human temporal bones, the extent of pneumatization is usually limited to the mastoid process, the perilabyrinthine region, and the petrous apex. In rare cases, epithelium may infiltrate the zygomatic process, articular eminence, squamous and occipital regions, or the area around the TMJ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations